Relationship of psychophysiological characteristics with different levels of motivation in judo athletes of high qualification - Korobeynikov, G. V.; Korobeynikova, L. G.; Romanyuk, L. V.; Dakal, N. A.; Danko, G. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2017)
Aim : to study the connection of psychophysiological characteristics with different levels of motivation in judo athletes of high qualification. Material: highly qualified athletes were examined, members of the National Judo Team (men). All athletes (n = 25) were divided into three groups, depending on the level of motivation to achieve success. Results: it is established that the high level of motivation for achieving success in judo is provided by activation of neurodynamic, cognitive functions and the level of light resistance. Athletes with a high level of motivation to achieve success is observed the predominance of the values of neurodynamic functions: endurance of the nervous system; speed of visual reactions. Athletes with an average level of motivation to achieve success identified higher values: productivity, speed, accuracy, effectiveness of verbal information. Athletes with a predominance of avoidance of failure motivation have a preference for other groups in the speed, efficiency and stability of the processes of thinking and processing information. Conclusions: judo athletes with a predominance of motivation to avoid a failure form coping strategy to prevent psycho-emotional stress. This helps to minimize the exhaustion of vegetative resources in conditions of extreme sports activity. Judo athletes with high level of motivation to achieve success, the presence of mental state of relative comfort is associated with the search for support among others and orientation toward internal beliefs.